Dislocation luminescence in highly doped degenerated germanium at room temperature - Arguirov, Tzanimir; Vyvenko, Oleg; Oehme, Michael; Schulze, Jörg; Kittler, Martin (Physica Status Solidi (C) Current Topics in Solid State Physics, 2013)
Dislocation related electroluminescence was detected in germanium p-i-n diodes grown on silicon using a virtual substrate. It appears at room temperature and above a certain threshold of the excitation current. The spectral feature characterizing dislocation related radiation consists of three peaks at around 0.45 eV. The appearance of the dislocation related peaks in the spectrum goes along with a change in the growth rate of the direct band-to-band luminescence upon increasing of the current through the structure. The observation is consistent with an injection of minority carriers in the p+ and n+ regions of the diode. As the p+ region contains the misfit dislocation rich virtual substrate it becomes a source of dislocation luminescence. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Dislocations; Germanium luminescence; Light emitting devices